PENGARUH ETIKA KERJA ISLAM TERHADAP KOMITMEN PROFESI INTERNAL AUDITOR, KOMITMEN ORGANISASI DAN SIKAP PERUBAHAN ORGANISASI PADA PERBANKAN SYARIAH DI KOTA PALEMBANG - BETRI, BETRI SIRAJUDDIN (Islamic Economics Program, Faculty of Islamic Economics and Business, 2016)
The purpose of this study was to determine the influence of the Islamic Work Ethic against internal auditor profession commitment, organizational commitment, and organizational change attitudes in Islamic banking in the town palembang.Jenis research is research asosiatip. The data used are primary data and the data in this study seconder. Populasi 9 (Nine) Islamic banking in the city of Palembang and the number of respondents were taken on the part of managers and some staff employees as much as 135 respondents. Data collection techniques by using literature, questionnaire and dokumentation. The analysis method used in this research is the analysis of qualitative and quantitative analysis. The results showed that the influence of Islamic work ethic commitment of the profession signipikan to internal auditors, and the work ethic signipikan Islamic influence on organizational commitment and work ethic signipican Islamic influence on attitude change organization.keywords: Islamic work ethic, commitment to the profession of internal auditors, organizational commitment, and organizational change attitudes